The Strategic Role of The Youth, Sports, and Tourism Office in Museum Devolepment Efforts Gubug Wayang Museum Mojokerto City - Ratih Maulidiyah; Ananta Prathama (International Journal of Social, Economic, and Business, 2025)
Gubug Wayang Museum Mojokerto City is one of the cultural tourism destinations that has an important role in the preservation of puppet art and culture. This study aims to analyze the role of the Youth, Sports and Tourism Office (Disporapar) in the development of the Gubug Wayang Museum using the role theory according to Iyas Yusuf (2014: 05) which includes the government as a regulator, dynamizer, and facilitator. The research method used is qualitative with informant retrieval techniques using purposive sampling and snowball sampling. The results showed that Disporapar's role 1) as a regulator in the preparation of policies and regulations related to museum management has been going well, 2) as a dynamizer by initiating educational programs and cultural promotions to increase the attractiveness of the museum is less than optimal, so it still needs to be improved again interesting programs, and 3) as a facilitator through the provision of facility assistance, budget funds, and cooperation with various parties has been running but still not optimal. The overall results show that it has been running well, but there are still challenges such as budget limitations, lack of community participation, and obstacles in digital promotion. Therefore, a strategy is needed to strengthen the role of Disporapar through optimizing policies, increasing cooperation with cultural communities, and utilizing digital technology in museum marketing to be better known by the wider community.